The CB1 receptor interacts with cereblon and drives cereblon deficiency-associated memory shortfalls - Carlos Costas-Insua; Alba Hermoso-López; Estefanía Moreno; Carlos Montero-Fernández; Alicia Álvaro-Blázquez; Irene B Maroto; Andrea Sánchez-Ruiz; Rebeca Diez-Alarcia; Cristina Blázquez; Paula Morales; Enric I Canela; Vicent Casadó; et al. (EMBO Molecular Medicine, 2024)
Abstract Cereblon/CRBN is a substrate-recognition component of the Cullin4A-DDB1-Roc1 E3 ubiquitin ligase complex. Destabilizing mutations in the human CRBN gene cause a form of autosomal recessive non-syndromic intellectual disability (ARNSID) that is modelled by knocking-out the mouse Crbn gene. A reduction in excitatory neurotransmission has been proposed as an underlying mechanism of the disease. However, the precise factors eliciting this impairment remain mostly unknown. Here we report that CRBN molecules selectively located on glutamatergic neurons are necessary for proper memory function. Combining various in vivo approaches, we show that the cannabinoid CB1 receptor (CB1R), a key suppressor of synaptic transmission, is overactivated in CRBN deficiency-linked ARNSID mouse models, and that the memory deficits observed in these animals can be rescued by acute CB1R-selective pharmacological antagonism. Molecular studies demonstrated that CRBN interacts physically with CB1R and impairs the CB1R-Gi/o-cAMP-PKA pathway in a ubiquitin ligase-independent manner. Taken together, these findings unveil that CB1R overactivation is a driving mechanism of CRBN deficiency-linked ARNSID and anticipate that the antagonism of CB1R could constitute a new therapy for this orphan disease.